Analisis Kemampuan Menyimak Dialog Berita Dan Petunjuk Pada Anak Sekolah Dasar (SD) - Arina Nur Salsabila; Zahrotun Siti Nur Kholimah; Shafira Azzahro; Fahrizal Akbaryanto; Sri Sukasih (LPPM Politeknik Pratama, 2023)
The research aims to analyze the listening skills of elementary school (SD) children in comprehending dialogue in news and instructions. It covers the ability to understand and respond to messages conveyed, including news dialogues and instructions for elementary school children. The research approach used is